The Pengelolaan Isu Unilever Pada Kasus PHK Masal: Pengelolaan Isu Unilever Pada Kasus PHK Masal - Meilina, Indah Meilina (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
PT Unilever Indonesia, which received negative news regarding the issue of layoffs in Indonesia various media. As many as 161 workers were laid off at the Rungkut factory in Surabaya. Is known The layoffs carried out by PT Unilever Indonesia were due to the company being transforming business operations. For the sake of the sustainability of the company, the company manage the issue so that it does not become a crisis. The purpose of this writing is to know the issue management carried out by Unilever in cases of mass layoffs usingthe theory and concept of reputation from Doorley and Garcia. This writing is compiled by the method of observation of mass media and social media. The result of the research is that Unilever perform 2 steps in the management of issues. First, by giving feedback then publish in the mass media the news of the layoff and claim the information that's not true. Unilever said it was only making adjustments to certain units in the company. Second, the company carries out a series of communications open with trade unions through two bilateral meetings for all employees through communication, outreach, being connected with affected employees. The company also offers various incentives, training, and support for willingness affected employees to remain productive after completing their tenure at company. In the future and also during the process, the company remains committed to open all lines of communication with employees and their unions.Keywords: Mass Layoffs, Issue Management, Reputation, Unilever